Sex-informed estrogen receptor modulation in schizophrenia: a male-focused ERβ/GPER1 framework for cognitive and negative symptoms - Carlson, John (Frontiers in Psychiatry, 2026)
Treatment-resistant schizophrenia (TRS) remains a major unmet clinical need, particularly in males who exhibit more severe negative and cognitive symptoms and limited responsiveness to dopamine-based therapies. Estrogenic signaling—especially through estrogen receptor beta (ERβ) and the G-protein–coupled estrogen receptor 1 (GPER1)—has emerged as a promising neuromodulatory target for these domains. This review synthesizes evidence supporting selective estrogen receptor modulators (SERMs), with an emphasis on raloxifene, as adjunctive agents capable of engaging central estrogenic pathways without feminizing systemic effects. Preclinical, stem cell–derived, and clinical data demonstrate that ERβ- and GPER1-mediated signaling enhances synaptic plasticity, mitochondrial stability, anti-inflammatory glial states, and dopaminergic–glutamatergic balance—core processes implicated in TRS pathophysiology. Complementary findings involving aromatase activity, neurosteroidogenesis, and genetic variation in ESR2 and CYP19A1 highlight opportunities for biomarker-guided stratification. The review also addresses ethical and gender-inclusive considerations, framing estrogenic modulation as sex-informed but not sex-restricted, given the universal expression of ERβ and GPER1 across sexes. Finally, emerging innovations—including GPER1-biased ligands, tissue-selective estrogen complexes, and nanoparticle delivery systems—are discussed as strategies to optimize central nervous system targeting while minimizing peripheral risk. Together, these insights position receptor-selective estrogenic modulation as a mechanistically grounded and clinically relevant approach for improving cognitive and negative symptom outcomes in TRS.